Screening of Nutritionally Important Components in Standard and Ancient Cereals - Vesna Dragičević; Milena Simić; Vesna Kandić Raftery; Jelena Vukadinović; Margarita Dodevska; Sanja Đurović; Milan Brankov (Foods)
Sustainable nutrition and food production involve dietary habits and farming systems which are eco-friendly, created to provide highly nutritious staple crops which could serve as a functional food at the same time. This research sought to provide a comprehensive analysis of whole-grain cereals, and some ancient grains toward important macro- (protein), micro-nutrients (mineral elements), and bioactive compounds, such as dietary fiber (arabinoxylan and β-glucan) and antioxidants (phytic acid, total glutathione, yellow pigment, and phenolic compounds) to provide functionality in a sustainable diet. Genotypes, such as durum wheat, triticale, spelt, emmer wheat, and barley, could be considered important and sustainable sources of protein (ranging 11.10–15.00%), as well as prebiotic fiber (β-glucan and arabinoxylan, ranging 0.11–4.59% and 0.51–6.47%, respectively), essential elements, and various antioxidants. Ancient grains can be considered as a source of highly available essential elements. Special attention should be given to the Cimmyt spelt 1, which is high in yellow pigment (5.01 μg·g−1) and has a capacity to reduce DPPH radicals (186.2 µmol TE·g−1), particularly Zn (70.25 mg·kg−1). The presence of phenolics, dihydro-p-coumaric acid, naringin, quercetin, epicatechin in grains of oats (Sopot), as well as catechin in barley grains (Apolon and Osvit) underline their unique chemical profile, making them a desirable genetic pool for breeding genotypes. This research provides a comprehensive assessment of different nutritional aspects of various cereals (some of which are commonly used, while the others are rarely used in diet), indicating their importance as nutraceuticals. It also provides a genetic background that could be translated the genotypes with even more profound effects on human health.